ESP (English for Specific Purрoses) TEACHING PROCESS, METHODS, ASSESSMENT AND ISSUES - Pardayevna, Kurbanova Niginabonu; Muxtorjonovich, Rakhmanov Sardor; NorinboevAbdurakhmonVoxidovich,; Sharofiddinqizi, Mukhiddinova Omina; o'g'li, Abduraimov Sardor Anvar; Xolmaxmatovna, Berdiyorova Shakhnoza (The journal of contemporary issues in business and government, 2021)
English for Specific Purposes (ESP) is generally defined as an approach to learning English which is based on the goals/needs of the learner. In context learning English in Uzbekistan at both high schools and universities, especially for students outside the English department, the ESP approach is a popular choice. The application of this approach is also in line with government policies in education which emphasize the objectives of learning English, namely to improve the ability of students to use English, especially for academic needs and professional careers with an emphasis on reading skills that allow students to understand authentic material topics according to their majors. This article puts forward a theoretical study regarding the basic concepts of ESP including its definition and role as a learning approach, along with related issues including needs analysis as the main feature of ESP, syllabus, learning objectives, materials, methodology, and evaluation of ESP-based English learning.